2015
DOI: 10.1016/j.mayocp.2015.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Separate Effects of Intensity and Amount of Exercise on Interindividual Cardiorespiratory Fitness Response

Abstract: For a fixed amount of exercise, increasing exercise intensity consistent with consensus recommendations eliminated CRF nonresponse. Low-intensity exercise may not be sufficient to improve CRF for a substantial proportion of sedentary obese adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
157
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(185 citation statements)
references
References 18 publications
(24 reference statements)
13
157
0
1
Order By: Relevance
“…CT had lower-intensity aerobic and resistance components than HIIT and RT, respectively. Approaches to improve exercise responses will have positive benefits on public health, and raising exercise intensity can increase the number of exercise responders (Ross et al, 2015). A previous work in younger adults demonstrated that 12 weeks of HIIT increased VO 2 peak and muscle citrate synthase activity to a similar extent as longer duration of lower-intensity aerobic exercise training (Gillen et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CT had lower-intensity aerobic and resistance components than HIIT and RT, respectively. Approaches to improve exercise responses will have positive benefits on public health, and raising exercise intensity can increase the number of exercise responders (Ross et al, 2015). A previous work in younger adults demonstrated that 12 weeks of HIIT increased VO 2 peak and muscle citrate synthase activity to a similar extent as longer duration of lower-intensity aerobic exercise training (Gillen et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Combined training (CT) offers many benefits of both aerobic and resistance training, although the intensity of aerobic and resistance components are lower than either HIIT or standard RT programs (Irving et al, 2015). Lower exercise intensity may limit training adaptations (Ross et al, 2015), particularly of mitochondria (MacInnis et al, 2016). A comprehensive approach to different exercise programs and the specific physiological and molecular adaptations and the potential impact of age on these adaptations remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The biological variability for insulin measures has been documented at upwards of 50–60% [4, 7]. We [8, 9] and others [2, 10] argue that a true treatment benefit for a given individual would be a response that exceeds the random day-to-day variability of measurement. Consideration of whether an exercise regimen has effects on glucose and insulin metabolism that is beyond the biological and analytical variability, as measured by technical error, is another neglected aspect of intervention trials.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, results of time course changes have traditionally been reported as only group means and standard deviations with individual time course changes not being reported. Based on a review of the literature, there have only been two studies to identify individual time course changes [44, 45]. Reporting of individual time course changes for VO 2 max and cardiometabolic risk factor measurements will help to further understand the individual variability in training responsiveness.…”
Section: Discussionmentioning
confidence: 99%